1540Mental health of Australian women before and during the COVID-19 pandemic. (2nd September 2021) - Dawadi, Shrinkhala; Meehan, Edward; Boyle, Jacqueline; Enticott, Joanne; Lim, Siew
Abstract: Background: The COVID-19 pandemic is associated with increased psychological distress in Australia and globally. Few studies have examined distress in women, a group vulnerable to experiencing increased financial and child-care stressors during the pandemic. Such epidemiological benchmark data is essential for population monitoring, and can inform policy by highlighting groups at increased risk of mental health burdens. Methods: Analysis of women aged 18-50 from a nationally representative survey collected in October 2020 (n = 1005) and the 2017-18 National Health Survey (n = 4267). Trends in the prevalence of very high scores on the Kessler-10, a measure of psychological distress capturing symptoms of affective and anxiety disorders, were compared across the surveys and by sociodemographic characteristics (age, education, socioeconomic status, income, family type and employment change). Results: Rates of very high psychological distress were 4.6% in 2017-18 (95% CI = 3.8%-5.4%) to 19.3% in 2020 (95% CI = 16.9%-21.8%), and were greater in 2020 across all sociodemographic subgroups. In 2020, rates were highest in women who experienced employment change (29.8%, 95% CI = 24.1%-35.6%), earned $0-$49, 000 annually (25.7, 95% CI = 18.5%-32.9%), and were single with children (24.8%, 95% CI = 16.3%-33.2%). Conclusions: Psychological distress has increased in Australian women during the pandemic, especially for those experiencing employment change, with lower incomes, or who are single parents. Findings will be discussed in the conjunction with extant social policies and access to mental health support. Key messages: The rate of very high psychological distress has increased fourfold in Australian women during the pandemic.